2001
DOI: 10.1002/1521-3919(20010201)10:2<117::aid-mats117>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for the Evolution of the Molecular Weight Distribution of Polymers During Ultrasonic Chain Scission

Abstract: A new model for ultrasonic scission of polymer chains has been developed. The model takes the coiled nature of the polymer chains into consideration. The time evolution of the molecular weight distribution for several values of the solvent quality parameter is obtained using the new model. It is seen that the model leads to higher scission rates and lower final molecular weights for better solvents in accord with the experiments. Simulated gel permeation chromatography results are also in line with the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Models for describing the molecular weight evolution during sonication include those of Schmid, [21,22] Baramboim, [23] Ovenall et al, [24] Rodriguez and Winding, [25] El'tsefon and Berlin, [26] Harrington and Zimm, [27] Glynn and Van der Hoff, [13,14] Doulah, [15] Malhotra, [28] Madras and Chattopadhyay, [29] Giz et al, [30] Tang and Liu [31] in historical order. Some of these models start from a scission mechanism and derive the molecular weight evolution from the proposed mechanism, while phenomenological ones describe the evolution of the molecular weight without proposing a scission mechanism.…”
Section: Theoretical Scission Modelssupporting
confidence: 84%
See 1 more Smart Citation
“…Models for describing the molecular weight evolution during sonication include those of Schmid, [21,22] Baramboim, [23] Ovenall et al, [24] Rodriguez and Winding, [25] El'tsefon and Berlin, [26] Harrington and Zimm, [27] Glynn and Van der Hoff, [13,14] Doulah, [15] Malhotra, [28] Madras and Chattopadhyay, [29] Giz et al, [30] Tang and Liu [31] in historical order. Some of these models start from a scission mechanism and derive the molecular weight evolution from the proposed mechanism, while phenomenological ones describe the evolution of the molecular weight without proposing a scission mechanism.…”
Section: Theoretical Scission Modelssupporting
confidence: 84%
“…Heterogeneous processes with a continuum of timescales, like dielectric relaxation and donor-acceptor energy transfer in fluorescence are commonly approximated by the stretched exponential function introduced by Kohlrausch in 1849. [43][44][45] The authors suggested that the average molecular weight evolution could be approximated as [30] …”
Section: Theoretical Scission Modelsmentioning
confidence: 99%
“…Numerous theoretical [77,78] and phenomenological models [79][80][81] for ultrasonic polymer degradation have been developed to evaluate the kinetics of the ultrasonic degradation process based on the reduction in the average molecular weight during the process [82]. Various models describing the molecular weight evolution during sonication have been presented in the work of Ovenall et al [78], Harrington and Zimm [83], Glynn and Van der Hoff [84,85], Doulah [86], Malhotra [87], Madras and Chattopadhyay [25], Giz et al [80] and Tang and Liu [88].…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Various models describing the molecular weight evolution during sonication have been presented in the work of Ovenall et al [78], Harrington and Zimm [83], Glynn and Van der Hoff [84,85], Doulah [86], Malhotra [87], Madras and Chattopadhyay [25], Giz et al [80] and Tang and Liu [88]. Some of these models start from a mechanism of scission and obtain the molecular weight evolution, while some describe the development of the molecular weight without proposing a scission mechanism.…”
Section: Kinetic Modelingmentioning
confidence: 99%
See 1 more Smart Citation